Penerapan Reinforcement Positif Terhadap Peningkatan Kehadiran Mahasiswa Dalam Kelas - Muhammad Rofiul Himam; Abida Dalla Maslacha; Muhammad Jamaluddin (Publikasi Inspirasi Indonesia, 2024)
Education is an important foundation in life, and discipline, including class attendance, is a key factor in achieving effective learning. This research aims to test the effectiveness of implementing positive reinforcement in increasing student attendance. The research method used was Classroom Action Research (PTK) with three cycles in class X UIN Malang. The main variables are student attendance as the dependent variable and the application of positive reinforcement as the independent variable. The results showed a significant increase in student attendance after implementing positive reinforcement. At the pre-research stage, 40% of students had poor discipline, 30% good, and 30% very good. After stage I, the percentage of excellent discipline increases to 50%. In stage II, better results were achieved with 70% of students showing very good discipline, and only 10% still lacking discipline. This data shows that positive reinforcement is effective in motivating students to be more disciplined in attending class. This research provides a theoretical contribution by enriching the literature on the influence of positive reinforcement in education and providing practical implications for education managers in designing strategies to increase student attendance. These results support the hypothesis that students who receive positive reinforcement show higher levels of attendance compared to those who do not receive reinforcement